Fostering social capital in a learning network: laying the groundwork for a peer-support service. (3rd March 2011) - Fetter, Sibren; Berlanga, Adriana J.; Sloep, Peter
In online learning environments, communities are desirable, or as is the case for a learning network, even essential. This raises the question of how to attain and sustain these communities. In this article, we argue that this can be achieved by fostering the social capital of the learning network. It is argued that this can be achieved by: 1) improving the relationship characteristics; 2) increasing the sense of belonging to the community; 3) heightening the mutual support. It is hypothesised that these improvements can be achieved by using so called Ad-Hoc Transient Groups (AHTGs). These groups are a means through which learners are brought together for a specific, learning-related goal ('ad-hoc') and for only a limited amount of time ('transience'). In order to deepen the concept of AHTGs, a relevant theoretical background as well as requirements for peer-support service that utilises Ad-Hoc Transient Groups is provided. This is followed by an example of how the service can be implemented in an existing learning network (eTwinning). Finally, conclusions are drawn and future research discussed.